Jamaican legislation and the Transatlantic Constitution, 1664-1839 - Graham, A (Cambridge University Press, 2017)
Between its first meeting in January 1664 and the final session held under unfree labour in December 1838, the volume of legislation passed by the house of assembly in Jamaica increased exponentially. As in Britain and Ireland, this reflected the growing administrative capacity and political power of the legislature and also the enormous demand for laws and law-making among local interest groups. The rise and fall of slavery and the slave society in the island was therefore underpinned in a large part by the power of its colonial legislature, which also operated within the broader transatlantic constitution structured by imperial politics and law. There was very little though to distinguish the house of assembly from others in British North America, at least in legislative terms, and even after the traumatic imperial disjuncture of 1783 the reformed transatlantic constitution continued to provide a supportive environment for the expansion of legislation within the island of Jamaica.